Validity and practicality of ethnovlog media on the production of typical Riau smoked fish (salai) as a science learning media - Sari, Ermina; Awal, Raudhah; Martalasari; Sudarmin (Universitas Negeri Jakarta, 2024)
Scientific studies on vlogs, ethnosciences, and social media literacy are current studies. A study on the development of ethno-vlog that raises local character and can be used as a learning medium is crucial. This study aims to develop a valid and practical ethno-vlog on the production of typical Riau smoked fish (salai fish) as a science learning media, especially in food preservation studies. The research is development research using a 4D development model (Define, Design, Develop, Disseminate). The ethno-vlog validity is carried out by disseminating questionnaires to 5 validators from three universities, namely Universitas Lancang Kuning, Universitas Negeri Padang, and Universitas Negeri Semarang, whereas the ethno-vlog practicality was conducted by three lecturers and 27 students of prospective Biology teachers at Universitas Lancang Kuning, Indonesia. The feasibility test results in that the ethno-vlog of food preservation in the production of typical Riau salai fish is valid and practical to be used as a learning media of food preservation for students of prospective Biology teachers at Universitas Lancang Kuning, Indonesia.